Lymphocyte alveolitis in HAM/TSP patients: preliminary report - K. Mattos; C. Queiroz; A.C. Peçanha-Martins; L. Publio; V. Vinhas; A. Melo (Arquivos de Neuro-Psiquiatria)
HTLV-I associated myelopathy has been described as a systemic disease characterized by manifestations in several organs outside the nervous system. We report inflammatory pulmonary involvement in patients with diagnosis of HAM.